EVALUATION OF ELECTRONIC MEDICAL RECORD FORMAT AND SECURITY SYSTEM IN DENTAL CLINIC OF THE GENERAL HOSPITAL IN BATAM CITY - Aurellia Vinta Aryanti Bintoro; Erdianto Setya Wardhana; Erna Dwi Agustin (Jurnal Medali, 2022)
Background: Electronic medical records in dentistry are the latest implementation in the health sector, especially dental health history to the services needed by patients by health care facilities and affect the format of dental medical records and electronic medical record security systems. This study aimed to review the completeness of the medical record format and the electronic medical record security system of the dental polyclinic of the General Hospital in Batam City. Method: This study used a descriptive cross-sectional observational design with two samples. Processing of data in the form of tables and texts as well as conclusions as a result of research.Result: The results showed that there were incomplete dental electronic medical record formats at Hospital A such as patient identity, required medical data, odontogram, intraoral examination, and treatment chart while Hospital B such as patient identity, required medical data, intraoral examination, treatment chart, and appendix. In the electronic medical record security system, the two samples did not meet the integrity and non-repudiation aspects.Conclusion: There is an incomplete dental electronic medical record format and security system in both samples according to the Indonesian Dental Medical Record Guidelines.